Casual inferences between participation in decision making, task attributes, work effort, rewards, job satisfaction and commitment - Scott-Ladd, Brenda; Travaglione, Tony; Marshall, Verena (Emerald Group Publishing, 2006)
Purpose – Regulatory frameworks in Australia encourage employee participation in decision making (PDM) on the basis that participation benefits work effort, job satisfaction and commitment. Although the literature supports this premise, there is little evidence that patterns of causal inference in the relationship are clearly understood. This study aims to examine for structural and causal inference between PDM and the work environment over time. Design/methodology/approach – Structural equation modeling was used to examine longitudinal, matched sample data for causal inferences. Findings – The paper finds that participation in decision making appears to promote job satisfaction and commitment, whereas task variety and work effort foster participation.Research limitations/implications – The use of quantitative, self report data, small samples and cross industry data as well as possible overlap between commitment foci may limit the transferability of the findings. It is also important to note causality is merely inferred. Practical implications – Although participation in decision making positively influences work effort, autonomy and commitment, practitioners need to be mindful of keeping a balance between employee and employer needs. Job satisfaction and commitment are at risk in the long term if participation is viewed merely as a survival strategy for coping with work effort and task variety. Originality/value – The paper examines inferred causality within a participative decision-making framework and addresses the previously neglected need for multi-site and longitudinal studies.